P40 Clinical simulations as a framework for delivering human factors education to foundation year 1 doctors. (November 2018) - Dandy, Ryan; Morrish, Samuel; Walker, Caroline
Abstract : Despite its evidenced effectiveness in clinical education, 1 simulation training is an underused resource in foundation doctor education at Milton Keynes University Hospital (MKUH). In addition, human factors (HF) training is a black hole in the foundation programme curriculum, despite its widespread use to promote safe and efficient working in other high-reliability organisations. A number of high profile cases have highlighted the importance of human factors training for healthcare professionals. 2 We aimed to fill both of these training voids with a human factors simulation programme aimed directly at FY1s at MKUH. After identifying key concepts and learning needs, we delivered an introductory lecture on the practical applications of HF theory. This included: communication skills, handover, bandwidth, leadership, raising concerns and situational awareness. Following this, a 12 week programme of weekly simulations training was delivered. This was based around common clinical scenarios often encountered by FY1s. All scenarios had been encountered by ourselves as FY1s. The main emphasis of the simulations was the real-time application of HF theory in a clinically relevant context. We designed 4 separate clinical scenarios pairing each with a key HF concept. We selected escalation to seniors, communication, situational awareness and bandwidth as the key learning points. We chose these as they were deemed the most applicable to everyday life as a junior doctor. These were conducted in a simulation suite with a 3G simulation manikin and trained simulation technicians. Senior ICM clinicians were present to observe and debrief on both clinical and HF components of each scenario. Session feedback was gathered via a questionnaire assessing; content, structure, presentation and environment, with each domain scored 1–5. In addition, the Debriefing Assessment for Simulation in Healthcare (DASH) tool was used by FY1s to assess the debriefing process. Although ongoing at the time of submission, feedback has been universally positive. Average score for session content was 9.7/10, whilst session structure averaged 14.2/15. A consolidation lecture has been arranged after which we will attempt to quantify FY1 confidence in the HF domains simulated, and how this has impacted on clinical practice. An understanding of human factors is essential for healthcare professionals to work safely and effectively; currently this plays a limited role in our foundation programme curriculum. We believe that this novel programme helps address these unmet educational and professional needs. We intend to expand and develop this programme to include multidisciplinary cohorts, across several local health trusts. References: Bullock A, Webb K. Technology in postgraduate medical education: A dynamic influence on learning?Postgraduate Medical Journal2015;91:646–50. doi:10.1136/postgradmedj-2014-132809 Bromiley M. The husband's story: From tragedy to learning and action. BMJ Qual Saf2015;24:425–7. doi:10.1136/bmjqs-2015-004129